A critical evaluation of virtual local government in Australia - Dollery, Brian (2003)
The vigorous debate surrounding local government amalgamation in Australia remains unresolved. In an attempt to break the current stalemate Percy Allan (2001) has proposed a model of `virtual local government' that seeks to combine the service appropriateness and effectiveness purportedly associated with demographically small councils with the service efficiency of large municipalities. This paper attempts to place his model in the context of the literature on the theory of public sector policy reform. It then goes on to examine virtual local government in the light of new institutional economics, public choice theory and the characteristics of Australian local government. - Reproduced.
Keywords: Local government - Australia; Local government